Distribuição e correlação espacial da incidência da fusariose em pimenta-do reino com atributos do solo - Drumond Neto, Antonio Pereira (2012)
The black pepper is one of the most important spices and consumed worldwide. The fusarium wilt is the major disease that attacks the pipericultura in Brazil and is caused by the fungus Fusarium solani f. sp. piperis (Nectria haematococca f. sp. piperis). Plant growth and root diseases are directly influenced by physical, chemical and biological soil environment, which are interconnected and form complex associations between them. The plant nutrition and a fertile soil with good physical characteristics influence all parts of the triangle of root diseases. New tools to investigate the variability and complexity of the interaction between the soil environment and pathogen are poorly studied, so the aim of this study was to research and implement methods of geostatistics to understand the distribution and spatial correlation of the intensity of Fusarium in black pepper crop with soil attributes. The experiment was conducted in the period from 2010 to 2011 in the North of Espírito Santo, Brazil. Geostatistics was used to study the spatial dependence and implanted a regular sampling grid of 12,000 m2. For the intensity of the disease was performed seven assessments, totaling 303 days, making the last evaluation soil samples for determinations chemistry, physics and texture. For the spatial correlation between disease severity with soil attributes, we used the analysis of variograms. The maps of the distribution of the disease over time show an initial focus on the edges of the crop, alongside a crop of older black pepper kingdom. The disease correlates spatially with the attributes fine sand ratio Mg / K, magnesium, pH, exchangeable acidity and base saturation.